2011
DOI: 10.1108/07378831111116958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating accessibility features of tutorial creation software

Abstract: Purpose -This paper seeks to compare the accessibility features and ease of use of three tutorial creation products -Camtasiaw 6 (by TechSmithw), Captivatew 4 (by Adobew), and VoiceThreadwto determine which product creates the most accessible tutorials. Design/methodology/approach -The paper tested the accessibility of the tutorials created using Camtasia, Captivate, and VoiceThread against the Voluntary Product Accessibility Templatew (VPATw) criteria. The tests were completed using JAWSw, a screen-reading so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Wakimoto and Soules (2011) evaluate major screencast creation software programs according to U.S. government guidelines for accessibility, and find that only two, Camtasia and Captivate, can create accessible screencasts. They point out that are many other tools for screencast creation available.…”
mentioning
confidence: 99%
“…Wakimoto and Soules (2011) evaluate major screencast creation software programs according to U.S. government guidelines for accessibility, and find that only two, Camtasia and Captivate, can create accessible screencasts. They point out that are many other tools for screencast creation available.…”
mentioning
confidence: 99%
“…An earlier article by Wakimoto and Soules (2010) reviewed three tutorial creation products for accessibility of their end products, and concluded that Camtasia and Captivate provided more accessible results but were more difficult to use. This finding was verified by Oud (2011), but she cautions that there are still potential barriers to accessibility even when using these two products and that these must be attended to by the tutorial's creator.…”
Section: S Hinesmentioning
confidence: 97%
“…Another criterion considered was the accessibility of the materials. Accessibility refers to the efforts to follow Section 508, in which educational institutions provide all students with equal access to campus information technologies (Wakimoto & Soules, 2011). This is to ensure that all students, regardless of (dis)ability, can succeed academically.…”
Section: Exploration Of Existing Interventionsmentioning
confidence: 99%